Cultural Landscapes Preservation and Social-Ecological Sustainability - Schmitz, María Fe; Herrero-Jáuregui, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Cultural landscapes are the result of social-ecological processes that have co-evolved throughout history, shaping high-value sustainable systems. The current processes of global change, such as agricultural intensification, rural abandonment, urban sprawl, and socio-economic dynamics, are threatening cultural landscapes worldwide. Whereas this loss is often unstoppable due to rapid and irreversible social-ecological changes, there are also examples where rationale protection measures can preserve cultural landscapes while promoting the sustainability of social-ecological systems. However, not all conservation policy-making processes consider the value of cultural landscapes, which makes their preservation even more difficult. Indeed, conservation policies focused on the wilderness paradigm are often counterproductive to conserving highly valuable cultural landscapes. The chapters in this book cover a wide spectrum of topics related to the preservation and sustainability of cultural landscapes, using different methodological approaches and involving regions from all over the world. This book can be useful for both researchers and professionals interested in using the socio-ecological framework in their scientific and applied work.